Front Cover: Embedded Isoreticular Zeolites: Concept and Beyond (Chem. Eur. J. 63/2017). Issue 63 (22nd September 2017) - Cho, Jung; Choi, Hyun June; Guo, Peng; Shin, Jiho; Zou, Xiaodong; Hong, Suk Bong
Abstract : The naming and building rules of body‐centered cubic embedded isoreticular zeolites (EIZs) with lta cage as the lattice point are presented. The procedures for the classification, description, and prediction presented herein will serve as a guideline for finding new EIZs and, eventually, for zeolites and related microporous materials with desired properties. More information can be found in the Full Paper by X. Zou, S. B. Hong et al. onpage 15922 .